Prioritising Responses Of Nurses To deteriorating patient Observations (PRONTO): a pragmatic cluster randomised controlled trial evaluating the effectiveness of a facilitation intervention on recognition and response to clinical deterioration. Issue 11 (21st April 2022) - Bucknall, Tracey K; Considine, Julie; Harvey, Gillian; Graham, Ian D; Rycroft-Malone, Jo; Mitchell, Imogen; Saultry, Bridey; Watts, Jennifer J; Mohebbi, Mohammadreza; Bohingamu Mudiyanselage, Shalika; Lotfaliany, Mojtaba; Hutchinson, Alison
Abstract : Background: Most hospitals use physiological signs to trigger an urgent clinical review. We investigated whether facilitation could improve nurses' vital sign measurement, interpretation, treatment and escalation of care for deteriorating patients. Methods: In a pragmatic cluster randomised controlled trial, we randomised 36 inpatient wards at four acute hospitals to receive standard clinical practice guideline (CPG) dissemination to ward staff (n=18) or facilitated implementation for 6 months following standard dissemination (n=18). Expert, hospital and ward facilitators tailored facilitation techniques to promote nurses' CPG adherence. Patient records were audited pre-intervention, 6 and 12 months post-intervention on randomly selected days. Escalation of care as per hospital policy was the primary outcome at 6 and 12 months after implementation. Patients, nurses and assessors were blinded to group assignment. Analysis was by intention-to-treat. Results: From 10 383 audits, improved escalation as per hospital policy was evident in the intervention group at 6 months (OR 1.47, 95% CI (1.06 to 2.04)) with a complete set of vital sign measurements sustained at 12 months (OR 1.22, 95% CI (1.02 to 1.47)). There were no significant differences in escalation of care as per hospital policy between study groups at 6 or 12 months post-intervention. After adjusting for patient and hospital characteristics, a significant change from T0 in mean length of stay between groups at 12 months favoured the intervention group (−2.18 days, 95% CI (−3.53 to –0.82)). Conclusion: Multi-level facilitation significantly improved escalation as per hospital policy at 6 months in the intervention group that was not sustained at 12 months. The intervention group had increased vital sign measurement by nurses, as well as shorter lengths of stay for patients at 12 months. Further research is required to understand the dose of facilitation required to impact clinical practice behaviours and patient outcomes. Trial registration number: ACTRN12616000544471p